If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9y+7=12y-4
We move all terms to the left:
9y+7-(12y-4)=0
We get rid of parentheses
9y-12y+4+7=0
We add all the numbers together, and all the variables
-3y+11=0
We move all terms containing y to the left, all other terms to the right
-3y=-11
y=-11/-3
y=3+2/3
| 7t+2t=t6 | | 0.25*x=1 | | 8=c–4 | | k+8=31 | | r=3.5 | | 2(7-8x)+3x=-7x-16 | | 9.18=3r | | 4k-8=12 | | x+8=+9 | | 9-2x-6x=-63 | | x+8=+) | | 105=5u+12 | | 10x+10=60000 | | 0,2t+3=t-1,8 | | -3=-10/p | | 12=12x-4-10x | | 1=-2m+9 | | 5w+4w=108 | | -8=-16+4n | | 4(3r-2)=16r | | X^2-15x+15=2 | | -56=6x+2x+8 | | 5c–3+2c=11 | | H=-16t^2+160t+3 | | 21=n−6 | | 7x=x+6+59/2 | | k3.5+7.4=8 | | 10y-1+7y-6=180 | | -6×+2y=-2 | | 2x-x=5x+5 | | 7x+6=6x-13 | | c÷2+16=36 |